Study on the Characteristics and Performance of Zhang Shuai’s Three Preludes - Cheng, Jie (Transactions on Social Science, Education and Humanities Research, 2023)
Since the reform and opening up, the exchange of music and culture between China and the West has become increasingly frequent. In the field of composition, a large number of outstanding modern Chinese composers have enthusiastically created many excellent works, among which Zhang Shuai’s "Three Preludes" is one of the representatives of modern Chinese piano works. In this work, Zhang Shuai combines Chinese ethnic music culture with Western modern music culture, giving the music a charm of combining Chinese and Western cultures, which has high research value. This article will mainly analyze and study the work from four aspects: the musical form and image analysis of the work, the creative characteristics of the work, and the analysis of performance skills. It will deeply explore how traditional Chinese ethnic music and Western jazz music elements can be cleverly integrated, and how to better interpret and interpret the work. It is hoped that this can provide readers with some valuable help and suggestions.